TEACHERS’ PERSPECTIVES ON THE IMPLEMENTATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN ENGLISH LANGUAGE TEACHING - Auliyah, Silmi; Abdul, Nurdevi Bte; Junaid, Junaid (Journal of Computer Interaction in Education, 2022)
This research aimed to find out the kinds of information and communication technology (ICT) used by the teachers to teach English at SMPN 3 Sungguminasa and the teachers’ perspectives on the implementation of information and communication technology (ICT) in English language teaching. The data were collected in February 2022 from 3 teachers of the seven and eight at SMPN 3 Sungguminasa. This research used a descriptive qualitative method, and the instruments used were observation and interview. The observation was used to observe and interview the English teachers of seventh and eighth grades at SMPN 3 Sungguminasa. The findings of this research show that the teachers used the kinds of ICT in English language teaching likewise, LCD, laptops, Mobile Phones, Microsoft Word, PowerPoint, E-Book, and YouTube. The result of the interview of this research showed that mostly the teachers gave positive perspectives and agreed that teachers use Information and Communication Technology (ICT) in English language teaching, they are happy, they are easy to understand the lesson, enthusiastic about ICT, motivated to learn, and diligent doing assignment